Does the Alternate Rapid Maxillary Expansion-Constriction/Reverse Headgear Therapy Enhance Pharyngeal Airway Dimensions? - Nivethitha Bhaskar; Shobha Sundareswaran; Latheef Vadakkeypeediakkal; Praveen Santhakumar; Sreehari Sathyanathan (Galenos Yayinevi, 2022)
Objective:The enhanced effect of maxillary protraction following the Alternate Rapid Maxillary Expansion-Constriction/Reverse Headgear (AltRAMEC/RH) protocol over the Rapid Maxillary Expansion/Reverse Headgear (RME/RH) protocol has been well documented. However, it is not known if the airway dimensions also follow a similar enhancement. This retrospective cohort study therefore aims to compare dimensional changes in the pharyngeal airway after maxillary protraction following RME/RH, versus AltRAMEC/RH.Methods: Pre- and post-treatment lateral cephalograms of 46 skeletal Class III patients with maxillary retrusion, who had undergone maxillary protraction using the AltRAMEC/RH or RME/RH protocol were compared for 20 dentoskeletal and airway variables. The waiting period of 6-8 months before initiating treatment served as the control period. The results were statistically evaluated using the paired t-test, the independent t-test, and the intraclass correlation coefficient.Results: The nasopharyngeal airway indicators in the AltRAMEC/RH group (PNS-ad1, PNS-ad2, UPD) showed a statistically significant mean increase of 2.09 mm, 2.74 mm, and 1.30 mm respectively. This was significantly more pronounced than the RME/RH group (P < .001). The control period did not show any significant change, thus showing the negligible effect of growth on the airway dimension. No significant changes were observed in the oropharyngeal airway indicators for both groups (P > .001).Conclusions: The AltRAMEC/RH protocol produced more significant improvement in the nasopharyngeal airway dimensions as compared to the RME/RH protocol. The changes in the oropharyngeal airway were insignificant with both the protocols.